2005
DOI: 10.1161/01.str.0000166050.84056.48
|View full text |Cite
|
Sign up to set email alerts
|

Vampire Bat Salivary Plasminogen Activator (Desmoteplase) Inhibits Tissue-Type Plasminogen Activator-Induced Potentiation of Excitotoxic Injury

Abstract: Background and Purpose-In contrast to tissue-type plasminogen activator (tPA), vampire bat (Desmodus rotundus) salivary plasminogen activator (desmoteplase [DSPA]) does not promote excitotoxic injury when injected directly into the brain. We have compared the excitotoxic effects of intravenously delivered tPA and DSPA and determined whether DSPA can antagonize the neurotoxic and calcium enhancing effects of tPA. Methods-The brain striatal region of wild-type c57 Black 6 mice was stereotaxically injected with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 30 publications
4
58
0
Order By: Relevance
“…In mice, when coinjected with NMDA into the striatum 6 or when administered intravenously 24 hours after NMDA-induced injury, 7 desmoteplase, in contrast to rtPA, does not promote excitotoxininduced neuronal death. This may be of particular importance given that endogenous tPA released within the cerebral parenchyma secondary to ischemia could have detrimental effects including enhancement of neurotoxic processes.…”
mentioning
confidence: 98%
“…In mice, when coinjected with NMDA into the striatum 6 or when administered intravenously 24 hours after NMDA-induced injury, 7 desmoteplase, in contrast to rtPA, does not promote excitotoxininduced neuronal death. This may be of particular importance given that endogenous tPA released within the cerebral parenchyma secondary to ischemia could have detrimental effects including enhancement of neurotoxic processes.…”
mentioning
confidence: 98%
“…However, the presence of fibrin and fibrinogen enhances its activity by 12,900 fold, which is much higher than that for t-PA. 113 Furthermore, bat-PA is inhibited by tranexamic acid, a synthetic lysine analog, that can be used to control any bleeding complications upon its administration. 114 In a canine model of arterial thrombosis, the bat-PA promoted effective, rapid and sustained reperfusion without systemic fibrinogenolysis in comparison with t-PA. 115 The use of bat-PA in the treatment of acute ischemic stroke does not promote excitotoxic injury which has been implicated during the administration of t-PA. 116 Desmoteplase administered after 3-9 h of symptom onset during the treatment of acute ischemic stroke showed a higher rate of reperfusion and better clinical outcomes compared with placebo. 117 125mg/kg was the most effective dose of desmoteplase for efficient reperfusion.…”
Section: (Iv) Monteplase (E6010)mentioning
confidence: 97%
“…In comparison with t-PA it does not promote excitotoxic injury. [99][100] Furthermore it should be possible to treat patients outside the time window of 3 h after symptom onset which was set for t-PA. In the Phase II studies DIAS and DEDAS, it was administered after 3-9 h and showed higher rate of reperfusion and better clinical outcome compared with placebo.…”
Section: Amediplasementioning
confidence: 99%